English Language Learners: Experiences of Teachers of Students with Visual Impairments who Work with this Population. (March 2013) - Topor, Irene; Rosenblum, L. Penny
Introduction: This article presents a study that gathered data from 66 teachers of students with visual impairments about their preparation to work with children who are visually impaired and are learning English, and their knowledge of instructional strategies and methods of instruction. Methods: An online five-part survey was available to teachers of students with visual impairments in the United States and Canada for a month-long period in the spring of 2012. Results: The 66 participants had various levels of knowledge of strategies for teaching English language learners. Many used common instructional strategies for English language learning when meeting their students' learning needs. When they taught braille to the students, they almost always taught in English. Thirty percent of the teachers did not feel qualified to work with students who are visually impaired and English language learners. Discussion: The participants were rich in their knowledge of strategies for teaching English, indicating that this group of self-selected individuals may have chosen to participate because the topic was of interest to them. Two-thirds of them felt qualified to work with students who are visually impaired and English language learners. Implications for practitioners: Teachers of students with visual impairments are often knowledgeable about educational strategies used with students who are learning English. They reported an overlap in strategies used with students who are visually impaired and students who are English language learners. When they teach braille, they most often do so in English braille. There is a need to duplicate this study with a wider cross section of teachers of students with visual impairments to ensure that the data reported here are representative of the population.